Asian ghost film vs. western horror movie Feng Shui - Baumgartel, Tilman (2015)
Access online through this link: https://www.plarideljournal.org/article/asian-ghost-film-vs-western-horror-movie-feng-shui
Keywords: Horror films; Film criticism; Feng Shui (Film)